(untitled) (Web of Discoveries: Journal of Analysis and Inventions, 2026)
This article presents a comparative analysis of the organization of school reviews and competitions in Uzbekistan, Finland, South Korea, and Russia. Drawing on regulatory documents, international assessment data (PISA 2022), and scholarly literature, the study identifies the pedagogical conditions, governance mechanisms, and assessment frameworks that underpin each country’s approach to academic olympiads, creative contests, and intellectual competitions in general education schools. The analysis reveals three distinct models: Finland’s non-competitive individual development model, South Korea’s high-stakes competitive model, and Uzbekistan’s hybrid model that combines centralized olympiad governance with diverse creative and intellectual contests. Based on the comparative findings, the article proposes evidence-based recommendations for enhancing Uzbekistan’s competition system through formative assessment integration, project-based competition formats, unified digital portfolios, and expanded international participation.